Laboratory friction and physical property measurements of halite/shale mixtures - Matt J Ikari (PANGAEA, 2020)
We simulate the lithification process in the laboratory by consolidating mixtures of halite and shale powders with halite-saturated brine. We quantify lithification by: (1) direct measurement of cohesion, and (2) measuring the porosity reduction of lithified samples compared to powders. We then compare the frictional properties of our lithified samples with powdered samples over a range of halite-shale proportions to systematically investigate the relationship between lithification and frictional slip behavior.